Using 3D anthropometric data for the modelling of customised head immobilisation masks - Loja, MAR (2019)
Projeto IPL/2016/SoftImob/ISEL; Projeto IPL/2016/CardiaCor_ESTeSL; Projeto LAETA_UID/EMS/50022/2019.